LIPASE ENZYME IMMOBILIZATION AT CELLULOSE NANOCRYSTALS (CNC) FOR LIPOLYSIS TRIGLYCERIDES - Ellys
Over the past decade, the technology of enzyme immobilization is being developed because it is able to produce reusable immobilized enzymes to reduce production costs. CNC (Cellulose Nanocrystal) is one of the biocomposites that can be employed as a matrix because proven to have high chemical stability, is environmentally friendly, and has low toxicity. This research aims to synthesize CNC from sugarcane bagasse as a matrix in immobilization of lipase enzyme to be applied in triglyceride lipolysis. The initial stage implemented in this study was to synthesize CNC from sugarcane bagasse using TEMPO oxidation method. Synthesize product then was used as a matrix in the immobilization of lipase enzymes through covalent bonding method. Immobilization process was conducted on 25°C dan pH 7 with immobilization period variation of 0,5–4,5 hours. The activity of the enzyme was analyzed by titrimetric method. The immobilized lipase enzyme will be utilized to catalyze lipolysis reaction of triglyceride from palm oil, with lipolysis period 2–10 hours, reaction temperature of 25–60oC, and pH of 6,25–11,25. Lipolysis products were analyzed by titrimetric method to obtain the degree of hydrolysis of the products. The result indicated that CNC from sugarcane bagasse had a sphere-shaped with diameter 94,7±7,65 nm, a degree of crystanillity of 80%, and initial degradation temperature of 220°C. Lipase enzyme was successfully immobilized at CNC so it can be utilized to catalyze lipolysis reaction with the highest degree of hydrolysis obtained was 10,1%. The optimum immobilization time and lipolysis was 1,5 hours and 6–8 hours respectively. Both free lipase and immobilized lipase had the optimum temperature at 40°C. There was optimum pH shift of lipolysis from pH 7,25 for free lipase to pH 8,25 for immobilized lipase.